Outcome and prognosis after adrenal metastasectomy: nationwide study. Issue 2 (20th April 2022) - Vlk, Elizabeth; Ebbehoj, Andreas; Donskov, Frede; Poulsen, Per Løgstrup; Rashu, Badal Sheiko; Bro, Lasse; Aagaard, Mikael; Rolighed, Lars
Abstract: Background: Data regarding adrenal metastasectomy are limited. Here, clinical outcomes, safety, and prognostic factors in patients undergoing adrenal metastasectomy were evaluated in a large nationwide study. Methods: Patients undergoing adrenal metastasectomy between 2000 and 2018 were identified in the Danish National Pathology Registry. Medical records were reviewed to confirm eligibility and to collect clinical data. The primary outcome was overall survival (OS). Cox multivariable regression analyses were? adjusted for baseline factors. Results: In total, 435 patients underwent adrenal metastasectomy; the primary cancer origins were renal ( n = 195, 45 per cent), lung ( n = 121, 28 per cent), colorectal ( n = 50, 11 per cent), and other ( n = 69, 16 per cent). The median (interquartile range; i.q.r.) age was 66 (59–71) years, and 280 (64 per cent) were men. The 5-year OS was 31 per cent. The 30-day mortality was 1.8 per cent. Complications were more frequent and severe in patients who underwent open surgery compared with laparoscopic surgery (Clavien–Dindo III–V, 31.5 per cent versus 11.8 per cent respectively, P < 0.001). Factors associated with poor survival included non-radical pR2 resection (hazard ratio (HR) 3.57, 95 per cent c.i. 1.96 to 6.48), tumour size more than 50 mm (HR 1.79, 95 per cent c.i. 1.26 to 2.52), lung cancer origin (HR 1.77, 95 per cent c.i. 1.31 to 2.40), open surgical approach (HR 1.33, 95 per cent c.i. 1.04 to 1.71), presence of extra-adrenal metastases (HR 1.31, 95 per cent c.i. 1.01 to 1.71), and increasing Charlson co-morbidity index factors (HR 1.14 per one-point increase, 95 per cent c.i. 1.03 to 1.27). Conclusion: Adrenal metastasectomy is safe and may result in long-term survival in a subset of patients. Non-radical resection, large tumour size, lung cancer origin, open approach, presence of extra-adrenal metastases, and co-morbidity were associated with inferior outcomes. Abstract : In this nationwide study, we identified all patients with resection of a metastasis in the adrenal gland. From the current results on long-term survival, the most suitable patients for surgery can be identified.